Optimization Of Wire And Tube Condenser In Refrigeration Cycle - Wan Mamat, Wan Mohd Fadhli (Universiti Sains Malaysia, 2004)
This thesis presents the experimental results of condenser that are commonly used in vapor compression cycle based on domestic refrigerators. The type of condenser that been used in this experiment is wire and tube condenser. A condenser was experimentally tested in a real refrigerator for some operating conditions. Based on an ideal performance of a wire and tube condenser, this experiment allowed a comparison between the actual result and the simulation one. The most important parameters that been measured is the temperature of the condenser surface at the point selected. This temperature will show whether the condenser operating at the required performance or not. Some change can be made to the condenser to make it operating at the maximum efficiency. In condenser optimization, the performance efficiency of the condenser can be change by changing the length and diameter of the wire and tube condenser. Pressure in the refrigeration cycle also influences the performance of the refrigerator. These things must be in a perfect set up in order to get a perfect operating refrigerator.